Aspek Religius dalam Pembaharuan Hukum Pidana melalui Politik Hukum Nasional - Brian Septiadi Daud; Awaluddin Awaluddin (Journal of Judicial Review, 2021)
The purpose of writing is to see about the Indonesian National Law System which is based on Pancasila, especially precepts I, and also to see the accommodation of religious aspects in carrying out Criminal Law Reform through National Law Politics. The research method used in this paper is normative juridical research. The results of research in creating a Pancasila-based legal system can be carried out by applying the juridical-religious principle (for the sake of justice based on divinity) not just a formality of decisions but a substantive / material justice. Then also the paradigm of legal thinking from positivistic to positistic-empirical, which is necessary to make genuine science and law enforcement more useful, including the use of a holistic approach by taking into account the conditions of society. And in carrying out a good reform of the National Criminal Law, it is better to look at religious-based aspects / values ​​and create policies that are in accordance with society in general.